Exploring the Potential Role of Moonlighting Function of the Surface-Associated Proteins From Mycobacterium bovis BCG Moreau and Pasteur by Comparative Proteomic - Pagani, Talita Duarte; Guimarães, Ana Carolina R.; Waghabi, Mariana C.; Corrêa, Paloma Rezende; Kalume, Dário Eluan; Berrêdo-Pinho, Marcia; Degrave, Wim Maurits; Mendonça-Lima, Leila (Frontiers in Immunology, 2019)
Surface-associated proteins from Mycobacterium bovis BCG Moreau RDJ are important components of the live Brazilian vaccine against tuberculosis. They are important targets during initial BCG vaccine stimulation and modulation of the host’s immune response, especially in the bacterial-host interaction. These proteins might also be involved in cellular communication, chemical response to the environment, pathogenesis processes through mobility, colonization and adherence to the host cell, therefore performing multiple functions. In this study, the proteomic profile of the surface-associated proteins from M. bovis BCG Moreau was compared to BCG Pasteur reference strain. The methodology used was 2D-gel electrophoresis combined with mass spectrometry techniques (MALDI-TOF/TOF), leading to the identification of 115 proteins. Of these, 24 proteins showed differential expression between the two BCG strains. Furthermore, 27 proteins previously described as moonlighting function were identified, 8 of these proteins showed variation in abundance comparing BCG Moreau to Pasteur and 2 of them presented two different domain hits. Moonlighting protein are multifunctional proteins in which two or more biological functions are fulfilled by a single polypeptide chain. Therefore, the identification of these proteins with moonlighting predicted functions can contribute to better understanding of the molecular mechanisms unleashed by live BCG Moreau RDJ vaccine components and improving its protection efficacy.